Rural-urban differences in the association between home-based community care services satisfaction and mental health status among older adults in Zhejiang Province, China: a cross-sectional study - Yuchen Ying; Yuchen Ying; Lifang Dong; Li Zhang; Fanqian Kong; Jiani Yang; Xiaoling Huang (Frontiers Media S.A., 2024)
ObjectiveThis study aims to examine the association between home-based community care services (HBCCS) and mental health in older adults and specifically analyzes rural-urban differences in the association.MethodsThis cross-sectional study enrolled 852 older adults from Zhejiang Province, China. The Patient Health Questionnaire (PHQ-9), 7-item Generalized Anxiety Disorder (GAD-7), University of California Los Angeles 3-item Loneliness Scale (UCLA-3), and the Mental Health (MH) component score of the 36-item Short Form (SF-36) were used to measure self-reported mental health status. Four categories of community care services were examined: daily, medical, social and recreational, and spiritual comfort. Satisfaction with community care services was assessed using self-reported measures. We used a multiple linear regression model.ResultsSatisfaction with daily care services, social and recreational services, and spiritual comfort services in rural older adults was significantly higher than in urban older adults (p = 0.016, p < 0.001, p < 0.001, respectively). Rural older adults reported lower scores on the PHQ-9, GAD-7, and UCLA-3 than urban older adults (p < 0.001, p = 0.003, p = 0.001, respectively) and had significantly higher scores on the SF-36 MH than urban older adults (p < 0.001). Among urban older adults, medical care services satisfaction was negatively related to the PHQ-9 and UCLA-3 scores (β = −0.296, p = 0.004; β = −0.447, p = 0.009, respectively). A lower UCLA-3 score was associated with higher levels of satisfaction with social and recreational services and with spiritual comfort services (β = −0.426, p = 0.010; β = −0.523, p = 0.002, respectively). A higher level of spiritual comfort services satisfaction was associated with a lower SF-36 MH score (β = 0.646, p < 0.001). Among rural older adults, medical care services satisfaction was negatively related to the GAD-7 score (β = −0.327, p = 0.028).ConclusionHome-based community care services satisfaction was positively associated with older adults' mental health status in Zhejiang Province. More attention should be paid to maintaining relevant satisfaction with HBCCS to ensure positive mental health among rural and urban older adults.